A shape memory copolymer based on 2-(dimethylamino)ethyl methacrylate and methyl allyl polyethenoxy ether for potential biological applications1. Issue 55 (17th June 2015) - Chen, Yangyang; Mo, Funian; Chen, Shaojun; Yang, Yan; Chen, Shiguo; Zhuo, Haitao; Liu, Jianhong
<x xml:space="preserve">Abstract</x> This study reports a novel shape memory copolymer synthesized with 2-(dimethylamino)-ethyl-methacrylate (DMAEMA) and methyl-allyl-polyethenoxy-ether (TPEG) for potential biological applications.